Violence and Peace: Creating a Culture of Peace in the Contemporary Context of Violence - Kochappilly, Paulachan (Asian Horizons, 2010)
Frampton F. Fox, ed., Violence and Peace: Creating a Culture of Peace in the Contemporary Context of Violence, Pune: CMS & Bangalore: Asian Trading Corporation, 2010, pages xiii + 392, ISBN: 81-7-86-535-2.